Unga inneliggande patienter med självdestruktivt beteende - Samuelsson, Margareta; Eidevall, Lena; Träskman-Bendz, Lil; Öjehagen, Agneta; Jensen, Ralf (Socialmedicinsk tidskrift, 2009)
Inom Division Psykiatri vid USiL(Universitetssjukhuset i Lund) har ett projekt genomförts i syfte att föreslå åtgärder för patienter med självskadebeteende. Projektet omfattade två delar – en journalgenomgång av 24 patienter, 15-25 år, inlagda under en sexmånadsperiod vid divisionens vuxen- och barnpsykiatriska kliniker och en intervjuundersökning av 14/24 patienterna och deras anhöriga. Av journalgenomgången framkom bl.a. att många patienter haft en svår uppväxt, utsatts för sexuella övergrepp och kände sig övergivna. I intervjuerna framkom att många upplevde att de inte fått någon behandling utan att inläggningen varit en fråga om förvaring. De få som fått DBT upplevde denna behandling positivt. A study was conducted at Lund University Hospital in 2001-2002 with the purpose to suggest alternative models for treatment and care of patients with deliberate self-harm behaviour. A review of the inpatient charts was conducted for twenty-four young female patients, 15-25 yrs of age, admitted to a child and adolescent or adult psychiatric clinic during a 6 month period, and 14/24 of the patients and their relatives were interviewed. Chart reviews showed that a lot of information that might be necessary in order to understand, diagnose and treat these patients is not always available. Furthermore, there is seldom a systematic, structured care and treatment planning for this group of young, mostly female patients. Many of the patients reported a difficult upbringing, had been subjected to sexual abuse and felt abandoned. In the interviews the lack of continuity was a recurrent complaint and the young women saw the days at the wards as long, tedious, empty and destructive, with little or no daily structure. The patients who had experienced DBT were very satisfied with this treatment. We conclude that treatment of deliberate self-harm must begin with thorough information on symptoms, life events and the current life situation. Emphasis must be put on a structured outpatient treatment model, including the treatment of existing psychiatric disorders, and the use of DBT or CBT. The principal aim must be to minimize the need of inpatient treatment. A model must also contain guidelines for a structured inpatient treatment.